PENGARUH INTERNET BANKING, KUALITAS LAYANAN, REPUTASI PRODUK, LOKASI, TERHADAP LOYALITAS NASABAH DENGAN INTERMEDIASI KEPUASAN NASABAH - ADINOTO NURSIANA (Jurnal Keuangan dan Perbankan, 2015)
Customer loyalty is one of the important factor that affect the growth of the bank. This research examined the effect of internet banking, service quality, reputation, product, and location on customer loyalty with the intermediation customer satisfaction. As analycal tool in this research is using software LISREL 8.80.Result from this research. first, internet banking has a negative and not significant impact on customer satisfaction and customer layalty, second, service quality, reputation, product, and location have a positif and significant impact on customer satistaction, but its have a negative and not significant impact on customer layalty, third, customer satisfaction has a negative and not significant impact on customer loyalty. So as to enhance customer loyalty, banks need to provide the best relationship between banks marketer and customer.